Satisfacción laboral de los funcionarios del área administrativa del gobierno autónomo descentralizado de Cotopaxi. - Cerón Hernández, Brando Raimon (2023)
This graduation project was carried out at the Decentralized Autonomous Government of Cotopaxi (GADPC) in order to determine the level of Job Satisfaction (JS) among employees in the Administrative Area of GADPC. The study included a theoretical review, assessment of the degree of satisfaction, and proposals for improvement strategies. The adopted methodology involved a quantitative approach with a descriptive scope. A cross-sectional study design was used to collect information at a single point in time. An instrument consisting of 9 dimensions called the Job Satisfaction Survey by Paul Spector was administered. The dimensions corresponding to the instrument were: payment, supervision, benefits, job itself, coworkers, communication, promotion, operational procedures, and rewards. The questionnaire was applied online to 40 institution employees who volunteered. Quantitative-descriptive analysis was conducted using SPSS 23. The results reflect a diverse distribution of ratings, highlighting areas of strength and areas for improvement. While a substantial percentage of employees report high or moderate satisfaction in aspects like payment, supervision, job itself, coworkers, communication, and benefits, it is evident that there is room for improvement in the dimensions of promotion, operational procedures, and rewards. Therefore, improvement strategies were proposed to increase the JS among GADPC workers. These findings should contribute to the strengthening of JS in the context of the public sector, fostering future research and actions aimed at optimizing and enhancing JS for workers in this institution.